Construction of PARI public health education programs for Chinese undergraduates: a Delphi study - Kong, Yuzhe; Xu, Haitao; Li, Chuyan; Yang, Yang; Zhu, Xiaoyi; Zuo, Yu (Frontiers in Public Health, 2024)
The objective of this study is to develop a consensus among experts on a comprehensive and scientifically sound physical activity-related injuries (PARI) public health education program specifically tailored for undergraduates.: This study designed three rounds of expert consultation by using a Delphi method. A panel of 30 experts from the fields of public health education, sports medicine, anesthesia pain, emergency medicine, and emergency nursing participated in the study. Results: This study successfully established a consensus among experts on the goals, content, teaching methods, and time allocation for the PARI Public Health Education Program for undergraduates. The program encompasses ten objectives divided into 2 main categories: professional knowledge and skill goals. In terms of content, it includes 5 primary indicators (Risk Indicators in Sports, Fitness Tests, Activities before and after exercise, Handling of discomfort during exercise, RICE principal content and application), 22 secondary indicators, and 56 detailed tertiary indicators. 6 teaching methods were identified as suitable, including PARI Prevention Workshop, Video Analysis and Discussion, Experiential Learning, Infographics and Visual Aids, Online courses and resources and Reflections and journal entries. Additionally, a typical 60-minute educational session was segmented into eight parts (Activity Opening and Introduction, Risk of cardiovascular events during exercise and its indicators, Fitness Testing and Risk Reduction, Preparation and recovery activities before and after exercise, Symptoms and emergency treatment during exercise, RICE principle, Interactive Q&A and Summary, End of the program and thank you), with a proposed time arrangement for each, ensuring comprehensive coverage of all topics.The consensus achieved in this study on the PARI Public Health Education Program for undergraduates lays a crucial foundation for the advancement of health literacy and proactive health management within this demographic. We